1990
DOI: 10.1002/mus.880130214
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic and morphological functional compensation in late poliomyelitis

Abstract: Patients with prior poliomyelitis may experience muscle function deterioration decades after onset of disease. The present study is aimed at describing electromyographic and morphometric evidence of muscular compensation and of on-going muscular instability. Ten subjects 42-62 years of age with onset of polio 25-52 years earlier were studied with macro EMG, single-fiber EMG (SFEMG), muscle strength measurement, and morphometrical analysis of muscle biopsies from the vastus lateralis muscle. SFEMG revealed incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
0
2

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 14 publications
5
24
0
2
Order By: Relevance
“…33 Differences in patient material and electrophysiological techniques may explain existing discrepancies. As shown in our previous reports 11,26 from the same group of polio subjects as in this study, reinnervation causes large motor units, sometimes very large. They increase in size with time in most cases, which has been attributed to an ongoing denervation-reinnervation process.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…33 Differences in patient material and electrophysiological techniques may explain existing discrepancies. As shown in our previous reports 11,26 from the same group of polio subjects as in this study, reinnervation causes large motor units, sometimes very large. They increase in size with time in most cases, which has been attributed to an ongoing denervation-reinnervation process.…”
Section: Discussionmentioning
confidence: 50%
“…Subjects acknowledging new weakness, had also lost significantly more strength than other individuals. As already demonstrated in our initial studies, 11,14 the polio-affected muscles were characterized in macro EMG by large motor units, with an 11-fold amplitude increase compared with age-matched control values. The muscle fiber areas were large, on average close to twice control values.…”
mentioning
confidence: 54%
“…Prior longitudinal studies have assessed muscle strength in one leg as "the worst"; however, the muscle strength in those studies was in general higher than in the present group of individuals, which could be a factor explaining the different findings. It is not known whether the lack of demonstrated reduction in muscle strength in our study corresponds to stable compensatory mechanisms (re-innervation and muscle fibre hypertrophy) (25). This can also be caused by altered relative contribution of these mechanisms or reflect that a deterioration in function could be influenced and/or delayed by a change in lifestyle with less physical activity.…”
Section: Discussionmentioning
confidence: 78%
“…These findings indicate pronounced reinnervation as compensation for the loss of motor units, as has been shown by Einarssen et al 4 who demonstrated that in late poliomyelitis concomitant macro-EMG study with muscle strength measurements and morphometrical analysis muscle biopsies allows estimation of the extent of axonal loss even though the interpretation may be complicated by fiber atrophy o r hypertrophy. I n their study, when macro-MUP mean amplitude was about 6, the percentage of remaining motoneurons was about 30%, and when the amplitude was about 15 the percentage was about 20%.…”
Section: Discussionmentioning
confidence: 60%